Morphological, structural and hardness changes of human dental enamel irradiated with a Nd:YAG laser. (9th October 2018) - Afsheen, Sumera; Tahir, Muhammad Bilal; Iqbal, Tahir; Firdous, Shamsa; Rehman, Jalil-Ur; Khan, H M Noor Ul Huda; Abrar, Muhammad; Naeem, M; Rafique, Muhammad Shahid
Abstract: Laser technology has become an indispensable part of modern dental practice, used in conjunction with or as an addition to other techniques. This paper focuses on applications of lasers in caries progression and surface hardness/acid resistance and the laser settings needed for clinical application. Enamel of human molar teeth was treated with a Nd:YAG laser (1064 nm) with varying numbers of laser pulses. The corresponding changes induced in the morphology, chemical composition, hardness and structure of human enamel were characterized by scanning electron microscopy, Fourier transform infrared spectroscopy, the Vickers hardness test and x-ray diffractometry, respectively. Etching, eruption, melting, recrystallization and cracking were observed in the morphology of enamel, while the hardness of the material increased as the number of pulses was varied. A decrease in intensity position of the hydroxyl group was observed, which is associated with the chemical change. The carbonate content also decreased, which accounts for the increase in acid resistance, but no such difference was observed in the phosphate content. A slight difference in lattice constant was also observed due to loss of structural water from hydroxyapatite. The results show that lasers can be additional resource in controlling the progression of caries in enamel.